2010
DOI: 10.2175/193864710798193941
|View full text |Cite
|
Sign up to set email alerts
|

Microwave UV Comes to Texas?

Abstract: The North Texas Municipal Water District (NTMWD) is looking to install ultraviolet light (UV) disinfection at the Floyd Branch Regional Wastewater Treatment Plant (Floyd Branch). Treatment plant staff is intrigued by the performance and ingenuity of the latest microwave UV reactor manufactured by Severn Trent Water Purification (Severn Trent), the MicroDynamics TM UV System. Before including the MicroDynamics TM UV System as one of several qualified bidders for their project, and because the technology is rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Virgadamo et al (2010) presented a case study that showed different procurement processes and assumptions made resulted in significantly different maintenance costs for UV systems at a treatment plant. A pilot-scale study was conducted and reported for a microwave UV system in Texas (Victor et al, 2010).…”
Section: Disinfection Methodsmentioning
confidence: 99%
“…Virgadamo et al (2010) presented a case study that showed different procurement processes and assumptions made resulted in significantly different maintenance costs for UV systems at a treatment plant. A pilot-scale study was conducted and reported for a microwave UV system in Texas (Victor et al, 2010).…”
Section: Disinfection Methodsmentioning
confidence: 99%